Chemical and Structural In-Situ Characterization of Model Electrocatalysts by Combined Infrared Spectroscopy and Surface X-ray Diffraction - Brummel, Olaf; Jacobse, Leon; Simanenko, Alexander; Deng, Xin; Geile, Simon; Gutowski, Olof; Vonk, Vedran; Lykhach, Yaroslava; Stierle, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2023)
New diagnostic approaches are needed to drive progress in the field of electrocatalysis and address the challenges of developing electrocatalytic materials with superior activity, selectivity, and stability. To this end, we developed a versatile experimental setup that combines two complementary in-situ techniques for the simultaneous chemical and structural analysis of planar electrodes under electrochemical conditions: high-energy surface X-ray diffraction (HE-SXRD) and infrared reflection absorption spectroscopy (IRRAS). We tested the potential of the experimental setup by performing a model study in which we investigated the oxidation of preadsorbed CO on a Pt(111) surface as well as the oxidation of the Pt(111) electrode itself. In a single experiment, we were able to identify the adsorbates, their potential dependent adsorption geometries, the effect of the adsorbates on the surface morphology, and the structural evolution of Pt(111) during surface electro-oxidation. In a broader perspective, the combined setup has a high application potential in the field of energy conversion and storage.
CRIS-Team Scopus Importer:2023-10-20

Modifying the Electrocatalytic Selectivity of Oxidation Reactions with Ionic Liquids - Yang, Tian; Yang, Juntao; Deng, Xin; Franz, Evanie; Fromm, Lukas; Taccardi, Nicola; Liu, Zhi; Görling, Andreas; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Angewandte Chemie International Edition, 2022)
The "solid catalyst with ionic liquid layer" (SCILL) is an extremely successful new concept in heterogeneous catalysis. The idea is to boost the selectivity of a catalyst by its modification with an ionic liquid (IL). Here, we show that it is possible to use the same concept in electrocatalysis for the selective transformation of organic compounds. We scrutinize the electrooxidation of 2,3-butanediol, a reaction which yields two products, singly oxidized acetoin and doubly oxidized diacetyl. When adding the IL (1-ethyl-3-methyl-imidazolium trifluormethanesulfonate, [C(2)C(1)Im][OTf]), the selectivity for acetoin increases drastically. By in situ spectroscopy, we analyze the underlying mechanism: Specific adsorption of the IL anions suppresses the activation of water for the second oxidation step and, thus, enhances the selectivity for acetoin. Our study demonstrates the great potential of this approach for selective transformation of organic compounds.
CRIS-Team WoS Importer:2022-06-03

Particle Size and Shape Effects in Electrochemical Environments: Pd Particles Supported on Ordered Co3O4(111) and Highly Oriented Pyrolytic Graphite - Kastenmeier, Maximilian; Fusek, Lukáš; Deng, Xin; Skala, Tomas; Mehl, Sascha; Tsud, Nataliya; Grau, Sebastian; Stumm, Corinna; Uvarov, Vitalii; Johanek, Viktor; Libuda, Jörg; Lykhach, Yaroslava; et al. (Journal of Physical Chemistry C, 2022)
Particle size and shape effects control the oxidation behavior of nanostructured electrocatalysts. We investigated the oxidation state of Pd nanoparticles supported on Ar+-sputtered highly oriented pyrolytic graphite (HOPG) and well-ordered Co3O4(111) films on Ir(100) as a function of electrode potential by means of synchrotron radiation photoelectron spectroscopy coupled with an ex situ emersion electrochemical (EC) cell. Scanning tunneling microscopy revealed the growth of hemispherical and flat Pd nanoparticles on Ar+-sputtered HOPG and Co3O4(111), respectively. The oxidation state of Pd nanoparticles is controlled by electronic metal support interaction (EMSI) associated with charge transfer at the interface. We found that the Pd nanoparticles are largely metallic on HOPG and partially oxidized on Co3O4(111). Specifically, we detected the formation of partially oxidized Pdδ+aggregates in combination with atomically dispersed Pd2+species. The latter species dominate at small Pd coverage and form the metal/oxide interface at high Pd coverage. Immersion into an alkaline electrolyte (pH 10, phosphate buffer) at potentials between 0.5 and 1.1 VRHEhas no significant effect for Pd/Co3O4(111) but yields traces of surface Pd oxide at 0.9 and 1.1 VRHEfor Pd/HOPG. Formation of PdO was observed at 1.3 and 1.5 VRHE. Quantitative analysis suggests nearly one monolayer and nearly two monolayers of PdO on the surfaces of the Pd nanoparticles supported on HOPG and Co3O4(111) at 1.5 VRHE, respectively. The differences in the oxidation behavior reveal the decisive role of the EMSI in the stability of the metal/oxide interfaces in an EC environment.
CRIS-Team Scopus Importer:2022-09-02